Precipitation behavior (1921 2000) in east La Pampa province (Argentina) (Semiárida, 2020)
The productive structure of the eastern region of La Pampa historically can be characterized as mixed agriculture, however, during the past two decades the area or summer crops expanded. Some studies show that the rainfall regime also varied during the same time span. This induced us lo think that there might be a causal relationship between the change in rainfall and the observed trend in the productive system. Therefore, a study or the rainfall variations during the time period 1921 to 2001 was conducted in order to evaluate their possible influence. The study area was divided into three zones: north, south and center. It was found that in all three zones the total annual rainfall during the growing season showed a positive trend. The highest proportion of rainfall increase was concentrated in the three summer months (EFM), while the lowest proportion corresponded to the winter months (JAS). During the studied period (1921 / 2001} all three zones presented a long cycle with humid and dry phases, separated by intermediate phases during the following time spans: 1) at the beginning of the evaluated period we observed the end of a transition phase from humid to dry. 2) A dry phase from 1930 to the end or the 940 decade. 3) A transition phase dry/humid between 1950 and the mid 70ties. 4) A humid phase which began in the 1970ties and had its climax during the 1990 decade, with posterior stabilization. These characteristics influence significantly on the regional production pattern, favoring summer crops. However, it should be taken into account that these changes might be reversible and since the region is a transition between the humid climates further east and the semiarid west, it present high vulnerability to the rainfall variations. This implies that precautions have to be taken for an eventual return to a period of lower rainfall.
Keywords: rainfall; eastern region of La Pampa; change; cycle